In R&D on Horticultural Crops… Epidemiology and decision support systems pave ways - Fry, William E; Small, Ian M; Danies, Giovanna (Indian Horticulture, 2019)
Several improvements to decision support system (DSS) are in process. One is to include in the system a functionality to enable it to be specific to the clonal linage in a region – to provide automated lineage-specific recommendations. For example, US-24 germinates indirectly more rapidly than does US-23 or US-8. We are currently modifying the DSS to take this type of detail into consideration. Once the user has identified which lineage is present, the forecast is adjusted to the characteristics of that particular lineage. Another feature currently in development is to take advantage of knowledge of location of active late blight (important in the USA, where late blight is sporadically active in time and space). If late blight has been reported within a few kilometers of your crop, the pathogen in that location could inoculate your crop. We are developing an algorithm for using that information in a risk assessment. If site X has been reported to have late blight, we can develop a risk prediction algorithm for a site Y nearby. The algorithm takes several factors into account: i) weather at site X (because weather at site X determines sporulation, release of sporangia and subsequent dispersal), ii) weather between site X and site Y (because this weather determines survival of sporangia in transit and direction of transit), and iii) weather at site Y because that weather determines survival of sporangia that have been deposited on crop and whether or not the sporangia will germinate and cause infection.